Monte Carlo modeling of spray agglomeration in a cylindrical fluidized bed: From batch-wise to continuous processes - Du, J.; Strenzke, G.; Bück, Andreas; Tsotsas, E. (Powder Technology, 2022)
Monte Carlo method is a stochastic approach that can simulate different micro-mechanisms occurring in spray fluidized bed (SFB) agglomeration. As no model covered the simulation of continuous SFB agglomeration process existing before, an event-driven constant volume Monte Carlo model is proposed. By adding particle feed and discharge events that take place periodically, the Monte Carlo model is extended to simulate continuous SFB agglomeration process. In these events, new particles are fed, and individuals are randomly selected and removed according to the feed rate and the change in bed mass. The experimental results show that the decrease of feed rate or bed mass increases the particle size. The comparison of experimental and simulation results shows that the continuous Monte Carlo model can predict the evolution of the particle size distribution with collision frequency prefactor 0.05 and breakage probability 0.17%. The development of bed mass in experiments can be reproduced in the simulations. (c) 2021 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2021-11-26